Oil palm shell lightweight concrete containing high volume ground granulated blast furnace slag - Shafigh, P.; Jumaat, Mohd Zamin; Mahmud, Hilmi; Alengaram, Ubagaram Johnson (Elsevier, 2013)
With the ever-increasing industrialization and urbanization, huge amounts of natural resources are required to make concrete. Green concrete can provide a solution to reducing the negative impact of the concrete industry. This paper presents the results of experiments conducted to produce green structural lightweight concrete by using oil palm shell (OPS) as coarse aggregate, and ground granulated blast furnace slag (GGBFS) as a supplementary cementing material at 30, 50 and 70 replacement of cement, and exposed to different curing conditions. Depending on the curing condition, test results show the possibility of producing green structural lightweight aggregate concrete with 28-day compressive strength of 23-42. MPa. The strength and density of GGBFS OPS concrete decrease as the percentage replacement of GGBFS increases. Data also show that initial hot water curing significantly improve the compressive strength of oil palm shell lightweight concrete containing high volume GGBFS at early age while this curing method is not useful for oil palm shell concrete containing just ordinary Portland cement. By incorporating GGBFS, grades 30 and 35 OPS concrete with significantly lower cement content than previous studies can be produced.